Post-treatment Apical Periodontitis in Primary Non-surgical Root Canal Treatment: A Multiple Correspondence Analysis - SANCHEZ, JOSE ANTONIO; JIMENEZ, DANIEL IVAN; GARCIA-GUERRERO, CLAUDIA CARMINA (Iranian Endodontic Journal, 2023)
Introduction: The presented study aimed to characterise periapical disease in teeth with primary non-surgical root canal treatment in persistent or emergent categories and their risk association. Methods: A retrospective observational study that evaluated permanent teeth with primary non-surgical root canal treatment, was conducted clinically and radiographically for over one year. The following variables were analysed: gender, age, type and location of tooth, previous diagnosis, treatment conditions, and type of coronal restoration. The supplementary variables included the perspectives of the treatment outcome, such as Remains normal, Improvement, and Failure. Statistical analysis was performed using a univariate analysis that estimated the average and proportion for each factor according to the result of the primary non-surgical root canal treatment. The multiple correspondence analysis identified the hierarchy between active variables and their association with the results. Results: A total of 232 teeth in 155 participants were analysed. A χ2 value, (P=0.023) showed that the emergent disease is associated with patients around the age of 50. The multiple correspondence analysis identified a tendency of grouping between the emergent disease and the short filling category, followed by symptomatic pulpitis as a previous diagnosis. The persistent disease was associated with errors and overfillings. An inadequate root filling and taper density adversely impacted the treatment outcome. Conclusions: The length of obturation influenced the presence of failure. Short fillings were associated with emerging periapical disease. Errors and overfillings contributed to the persistent disease in the populations studied.